Diagnostic Accuracy of Procalcitonin for Differentiating Bacteraemic Gram-Negative Sepsis from Gram-Positive Sepsis - (:unkn) unknown (AVES, 2018)
Objective: The identification of bacteraemia in patients with suspected sepsis is crucial for survival. A cheap, fast and reliable biomarker, which can predict the causative pathogen group, may be useful to confirm or exclude the presence of bacteraemia. This study aimed to evaluate the relationship between procalcitonin (PCT) and the causative pathogen in intensive care patients with sepsis and bacteraemia. Methods: Patients with diagnosed sepsis, a positive blood culture and measured serum procalcitonin levels during their intensive care unit stay were included in the study. Demographic data, PCT level, leukocyte count, C-reactive protein level, creatinine level, lymphocyte count, leukocyte/lymphocyte ratio and the group of the pathogen that detected in the blood culture were retrospectively recorded. Results: Overall, 136 sepsis patients who were diagnosed with bacteraemia were included in the study. The PCT level was 7.31 ng mL(-1) in the gram-negative group and 0.46 ng mL(-1) in the gram-positive group. For PCT, the sensitivity was 70.83% and the specificity was 84.21%, with the cut-off value being <= 1.3. The area under the receiver operating characteristics curve for PCT was 0.80. Conclusion: Patients with gram-negative sepsis had higher PCT values than those with gram-positive sepsis. Our results suggest that PCT value may be a useful tool for distinguishing between gram-negative and gram-positive bacteraemia.
Keywords: Sepsis; procalcitonin; bacteraemia; INFLAMMATION